Soft-error tolerant design for satellite-board computations - Zhang, Lei (2016)
High energy particles in the outer space could flip the state of the latches of the electronic devices. The upset of the latches is called soft error since it would not cause permanent damage to the device. However, the soft error may cause faults in a processor and lead to malfunction of the computer system on the satellite.